Properties of Electrospun Aligned Poly(lactic acid)/Collagen Fibers with Nanoporous Surface for Peripheral Nerve Tissue Engineering. Issue 10 (21st July 2022) - Xu, Tao; Zhang, Xu; Dai, Xiu
Abstract: It is important for the functional recovery of defective nerves to construct a suitable microenvironment for nerve regeneration by optimizing the topological structure and biological functions of nerve grafts. Electrospun fibers are employed to mimic the extracellular matrix (ECM) and the effect of the porous features on fiber surface draws much attention. Yet, little is known about the effect of the nanotopology of the fiber surface in conjunction with collagen I (COL) on neural cells. Herein, poly(lactic acid) (PLA)/COL hybrid fibrous membranes with a nanoporous structure on a fiber surface are fabricated. The performance of the obtained fibrous membranes is investigated by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), water contact angle (WCA), and tensile test measurements. The cytotoxicity and biocompatibility of PLA/COL hybrid fibrous membranes and their effects on neural cells are systematically investigated. The physicochemical test results show that the PLA/COL hybrid fibrous membranes have appropriate mechanical properties and improved hydrophilicity. The MTT assay and hemolysis assay suggest the nontoxicity and good hemocompatibility of PLA/COL membranes. The nanoporous structure on the fiber surface and the introduction of COL synergistically promote proliferation and elongation of Schwann cells (SCs) and the extension of dorsal root ganglion (DRG) neurites. Abstract : The aligned PLA/COL fibers with nanoporous surface are fabricated. The prepared fibers can promote the proliferation and elongation of Schwann cells and promote the extension of dorsal root ganglion cells neurites. They can also induce the oriented growth of neural cells. This work explores the potential use of the porous aligned fibrous membranes for peripheral nerve repair.